Analisis Kemampuan Pemecahan Masalah Peserta Didik SMA dalam Menyelesaikan Materi Statistika - Laila Diyatul Husna; Yanuar Rizki Hasibuan; Husnayani Husnayani; Ramadhani Ramadhani (Journal on Education, 2025)
The aim of this research is to evaluate high school students' ability to solve mathematical problems using statistics material. This study was conducted on 20 class XII students of Madrasah Aliyah Al-Washliyah 22 Tembung using a qualitative descriptive approach. Understanding the problem, planning a solution, implementing the solution, and checking the answer again are four indicators used to assess a person's problem solving abilities. The results show that the average student ability is in the medium category, with a diverse distribution. The absence of application of problem-based learning and contextual learning approaches is a factor in low ability. To improve students' understanding and ability to relate statistical concepts to real situations, this research suggests using more innovative learning approaches, such as problem-based learning and interactive technology.